A neuro-fuzzy system based on logical interpretation of if-then rules - Łęski, Jacek M.; Henzel, Norbert (Zielona Góra: Uniwersytet Zielonogórski)
Several important fuzzy implications and their properties are described on the basis of an axiomatic approach to the definition of the fuzzy implications. Then the idea of approximate reasoning using the generalized modus ponens and fuzzy implications is considered.
Keywords: neuro-fuzzy systems; soft computing; fuzzy implications; approximate reasoning